Pendampingan Kesehatan Fisik bagi Pembatik sebagai Upaya Mengurangi Risiko dan Keluhan Work-related Musculoskeletal Disorder (WMSD) di Kampung Batik Laweyan - Arif Pristianto; Tanjung Anitasari Indah Kusumaningrum; Mahendra Wahyu Dewangga; Fathul Wahid Ilmuddin; Mutiara Sabta Amanda; Ana Triasari; Muhammad Nizar Siddiq; Samiyem Samiyem; Khansa Nuriashinta Nabila (Warta LPM, 2024)
The high incidence of Work-related Musculoskeletal Disorder (WMSD) in workers is caused by various factors from the individual and the work environment. Musculoskeletal complaints in workers also occur and disrupt productivity for batik workers. Batik itself has several types and several divisions of work. Workload, duration, and poor work posture cause excess work on the muscles which results in functional disorders of the structural muscles in the neck and causes myofascial trigger point syndrome (MTPS). This service activity is carried out to resolve complaints, prevent further impacts, and increase worker productivity. The program is provided in the form of Integrated Neuromuscular Inhibition Technique (INIT) and Self Stretching combined with infrared radiation. Apart from that, educational efforts are also being made regarding Musculoskeletal Disorders and ergonomic working positions. Measurement of activity effectiveness is carried out using the VAS, NDI, NBM and WERA instruments. Based on the results of the activities carried out, it can be concluded that health assistance efforts for batik workers in Laweyan Batik Village in the form of providing therapeutic and educational measures have proven effective in reducing complaints and incidents of WMSD. By reducing complaints, the work output and productivity of batik makers increases.